The Effect of Roller Foam Massage on Decreasing Levels of Lactic Acid Post Exercise at Taekwondo Club - Eckel Putra Renanda Indragiri; Qorry Armen Gemael; Deden Akbar Izzuddin (Media Ilmu Keolahragaan Indonesia, 2023)
Abstract. This study focuses on the effect of using Roller Foam Massage on decline rate sour lactate after training at the Taekwondo Athlete Club YD Gor Fat Bekasi District . Taekwondo is art self-defense popular with challenges physically tall , however _ enhancement rate sour lactate can affect athlete performance and recovery . The purpose of this research is to evaluate is Roller Foam Massage technique can be effective in reducing rate sour lactate in athletes after exercise. Type research use an approach quantitatively with the one group pretest and posttest method . population as many as 16 players and using purposive sampling. With value based on data analysis obtained t-test and before has tested normality and homogeneity especially first . Normality test using Shapiro-Wilk the pretest results have a significance of 0.655 0.05 then the pretest data is normally distributed , and the normality test using the Shapiro-Wilk on the posttest results have a significant 0.111 0.05 , the posttest data is normally distributed . The homogeneity test has a sig value . 0.945 0.05 then it can be obtained data distribution is homogeneous. Then the Paired t test shows that the value of Sig. (2-tailed) of 0.001 0.05, it can be concluded that there is a real difference between the results of using roller foam massage on the Pretest and Posttest data.Abstract in Indonesia. Penelitian ini berfokus pada pengaruh penggunaan Roller Foam Massage terhadap penurunan kadar asam laktat pasca latihan pada Atlet Club Taekwondo YD Gor Tambun Kabupaten Bekasi. Taekwondo merupakan seni beladiri populer dengan tantangan fisik yang tinggi, namun peningkatan kadar asam laktat dapat mempengaruhi performa dan pemulihan atlet. Tujuan penelitian ini adalah untuk mengevaluasi apakah teknik Roller Foam Massage dapat efektif dalam mengurangi kadar asam laktat pada atlet setelah latihan. Jenis penlitian menggunakan pendekatan kuantitatif dengan metode one group pretest and postest . populasi sebanyak 16 pemain dan menggunakan purposive sampling. Dengan nilai berdasarkan analisis data memperoleh Uji-t dan sebelumnya telah diuji normalitas dan homogenitas terlebih dahulu. Uji normalitas menggunakan Shapiro-wilk hasil pretest memiliki signifikan 0,655 0,05 maka data pretest berdistribusi normal, dan uji normalitas menggunakan Shapiro-wilk pada hasil posttest memiliki signifikan 0,111 0,05 maka data posttest berdistribusi normal. Uji homogenitas memiliki nilai sig. 0.945 0.05 maka dapat diperoleh distribusi data adalah homogen.Kemudian Uji Paired t test bahwa nilai Sig. (2-tailed) sebesar 0,001 0,05, maka dapat disimpulkan bahwa terdapat perbedaan yang nyata antara hasil menggunakan roller foam massage pada data Pretest dan Posttest.